Synthesis of Schiff Bases of 2-amino-5-aryl-1,3,4-thiadiazole and Its Analgesic, Anti-Inflammatory and Anti-Bacterial Activity - Alok Pandey; R. Rajavel; Sandeep Chandraker; Deepak Dash (E-Journal of Chemistry)
Schiff Bases of 2-amino-5-aryl-1,3,4-thiadiazole derivatives have been synthesized with different aromatic aldehyde. 1,3,4-thiadiazole derivatives were prepared by the reaction of thiosemicarbazide, sodium acetate and aromatic aldehyde. The structures of the titled Schiff bases were elucidated by IR and 1H NMR spectral measurements. All the compounds were evaluated for their analgesic activity against swiss albino mice, anti-inflammatory activity against Wister albino rats. The compounds showed significant antibacterial activity against Staphylococcus aureus (gram-positive) bacteria and E. coli (gram-negative) bacteria.